2019
DOI: 10.1111/trf.15130
|View full text |Cite
|
Sign up to set email alerts
|

Additional filtering of blood from a cell salvage device is not likely to show important additional benefits in outcome in cardiac surgery

Abstract: BACKGROUND Several authors and manufacturers of cell salvage devices recommend additional filtering of processed blood before transfusion. There is no evidence to support this practice. Therefore, we compared the clinical outcome and biochemical effects of cell salvage with or without additional filtering. STUDY DESIGN AND METHODS The patients, scheduled for coronary artery bypass grafting, valve replacement, or combined procedures were part of our randomized multicenter factorial study of cell salvage and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Similarly, de Vries et al, in 2019, performed a comparison between Cell Salvage with and without filters. The results showed that the use of a filter did not increase the benefits of Cell Salvage in terms of reduced ICU days and hospitalization [ 29 ]. Along the same lines, Weltert et al in 2003 compared Cell Salvage with the cardioPAT system®.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, de Vries et al, in 2019, performed a comparison between Cell Salvage with and without filters. The results showed that the use of a filter did not increase the benefits of Cell Salvage in terms of reduced ICU days and hospitalization [ 29 ]. Along the same lines, Weltert et al in 2003 compared Cell Salvage with the cardioPAT system®.…”
Section: Resultsmentioning
confidence: 99%
“…In twelve RCTs, involving 2129 participants in both the intervention group (n = 1061) and the control group (n = 1068), the effectiveness of using the Cell Salvage was compared with the control group, where traditional methods based on allogeneic transfusion were employed. Five studies showed a high risk of bias [ 26 , 41 , 43 , 46 ], while one study demonstrated an adequate level of quality [ 29 , 33 , 34 , 36 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations